2017
DOI: 10.1016/j.jss.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

The independent effect of cancer on outcomes: a potential limitation of surgical risk prediction

Abstract: BACKGROUND Cancer patients are often thought to have worse surgical outcomes. There is a growing view that risk models do not adequately predict these outcomes. This study aims to compare the use of common risk models for benign versus malignant gastrointestinal disease. MATERIALS AND METHODS The NSQIP 2005–2015 participant use files were queried for patients undergoing elective surgery for benign and malignant diseases with a primary procedure code for major colon, pancreas, or stomach resection. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…They found that there was an increased likelihood of 30-day mortality (OR = 1.18, 95% CI = 1.10–1.28), complication rate (OR = 1.09, 95% CI = 1.07–1.11), and the total number of complications (OR = 1.08, 95% CI = 1.06–1.11) in patients undergoing surgery for cancer compared to benign lesions. 9 More patients in the Indian subset underwent major surgical procedures (65.7% vs 36%), and this may have been an additional factor associated with increased complication rate. Indian patients with complications were older, with ASA grade III and IV physical status, and underwent major surgeries, which are known risk factors for postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…They found that there was an increased likelihood of 30-day mortality (OR = 1.18, 95% CI = 1.10–1.28), complication rate (OR = 1.09, 95% CI = 1.07–1.11), and the total number of complications (OR = 1.08, 95% CI = 1.06–1.11) in patients undergoing surgery for cancer compared to benign lesions. 9 More patients in the Indian subset underwent major surgical procedures (65.7% vs 36%), and this may have been an additional factor associated with increased complication rate. Indian patients with complications were older, with ASA grade III and IV physical status, and underwent major surgeries, which are known risk factors for postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Longer hospitalizations are also associated with iatrogenic and hospital-acquired sequelae that contribute to increased morbidity and mortality [8]. Preoperative hypoalbuminemia (albumin <3.5 g/dL), body weight loss (>10 percent decrease in body weight six months prior to surgery), body mass index <18.5 kg/m 2 , dialysis status, disseminated cancer, increasing frailty, non-Caucasian race, perioperative anemia, blood transfusion, increasing operative time, age, and American Society of Anesthesiologists (ASA) classification have all been associated with prolonged LOS for various abdominal and gynecological surgeries [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively a cancer diagnosis has been shown to be an independent risk factor for a poor patient outcome with the previous series showing the poor utility of the ACS‐NSQIP calculator to predict complications in patients with cancer 21 . Leeds et al 21 reviewed the treatment out of 264 401 patients, of which 111 563 had a history of cancer, cancer patients had worse an outcome in every measure, and having a diagnosis of cancer at the time of surgery lead to an 18% increased odds of death, a 9% increased odds of a complication, and an 8% increased odds of multiple complications 21 . When focusing only on the outcome of patients undergoing a total joint arthroplasty in the setting of cancer Sloan et al 18 analyzed over 500 000 patients and found that cancer patients were at significantly increased risk of death and postoperative complications 18 .…”
Section: Discussionmentioning
confidence: 99%